Transformational Leadership and Healthcare Supply Chain Modernization: A Systematic Review and Research Agenda - Djoman, Djako A.; Thompson, David A. (Journal of Supply Chain Management Science, 2025)
This study investigates the relationship between transformational leadership and the healthcare supply chain modernization, particularly in light of the challenges posed by the COVID-19 pandemic. The introduction highlights the crucial role of leadership in adapting to the rapidly advancing digital environment, which is essential for maintaining competitiveness and resilience. This study addresses a gap in the literature concerning how transformational leadership can have an impact on supply chain modernization. The study concentrates on three principal databases, including Scopus, Web of Science, and PubMed to collect published papers. A total of 2,137 papers related to transformational leadership and supply chain management were initially identified. A systematic literature review was conducted, drawing on 22 peer-reviewed articles published between 2010 and 2025, focusing on transformational leadership and its impact on supply chain modernization. The methodology followed the PRISMA guidelines to ensure a rigorous selection process, analyzing the relationship between transformational leadership and key outcomes in supply chain performance. The findings from the included studies suggest several ways in which transformational leadership may influence aspects of supply chain modernization through knowledge sharing, digital transformation, and organizational agility.